2014
DOI: 10.2147/opth.s59208
|View full text |Cite
|
Sign up to set email alerts
|

Ocular alignment and refraction in preterm children at 1 and 6 years old

Abstract: PurposeTo investigate cycloplegic refraction and ocular alignment in a population of preterm children at 1 and 6 years old.Patients and methodsWe included 261 preterm infants with a birth weight ≤1,500 g and a gestational age ≤32 weeks; there were 217 preterm infants (group 1), 28 preterm infants with mild retinopathy of prematurity (ROP) (group 2), and 16 preterm infants affected by severe ROP (group 3). Each patient underwent retinoscopy, ocular alignment assessment, and fundus examination at 1 and 6 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, MSF can manifest in two forms: esotropia-hypotropia complex and exotropia-hypotropia complex. 1 This patient exhibited an esotropia-hypotropia complex form of MSF. In such patients, there is a supero-temporal dislocation of the posterior portion of the elongated globe from the muscle cone due to increased axial length.…”
Section: Descriptionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, MSF can manifest in two forms: esotropia-hypotropia complex and exotropia-hypotropia complex. 1 This patient exhibited an esotropia-hypotropia complex form of MSF. In such patients, there is a supero-temporal dislocation of the posterior portion of the elongated globe from the muscle cone due to increased axial length.…”
Section: Descriptionmentioning
confidence: 87%
“…However, MSF can manifest in two forms: esotropia–hypotropia complex and exotropia-hypotropia complex. 1 …”
Section: Descriptionmentioning
confidence: 99%
“…The first is physiological myopia due to premature birth and gestational stage, the second is myopia due to disruption in the development of the anterior segment, regardless of the development of PR, characterized by narrow anterior chamber angle, increased corneal curvature and spherical lens, and the third type is myopia that can range from mild to severe due to severe PR. [12] Studies have reported that although PR is not present in preterm cases, emmetropization is affected depending on gestational age and birth weight. In preterm cases, it was observed that as the gestational week decreased, myopic values increased and SE values decreased considerably.…”
Section: Discussionmentioning
confidence: 99%
“…In the study where Muna et al classified preterm cases as no PR, mild PR but not requiring treatment and requiring treatment, in their first age measurements, 3D and below hyperopia values were reported as 39.2%, 28.6% and 22%, respectively, while Akdoğan et al [5] reported that 2D and higher hypermetropia was 56.3% in preterms born below 36 weeks. [12] According to the studies conducted,it is showed that hyperopia values decreased in the preschool period. In the study conducted by Özdemir et al, [11] the incidence of hyperopia in premature children aged 5−7 years without ROP was reported as 21%.…”
Section: Discussionmentioning
confidence: 99%
“…Specific conditions such as prematurity and associated retinopathy may predispose to strabismus in the presence of myopia. 9 …”
Section: Introductionmentioning
confidence: 99%